Wilderness medicine : beyond first aid - Forgey, William W., 1942- (Falcon guide., 2012)
With help just a quick 911 phone call away, it's hard to imagine the consequences of experiencing an emergency in remte lands. Wilderness Medicine: Beyond First Aid is a comprehensive text for the recognition, treatment, and prevention of wilderness emergencies.